Deagriculturalisation and India’s trajectory toward net-zero: Analysing emission impacts using bayesian vector autoregression - KARIMZADEH, MAJID; AHMAD, FARAZ (The Indian Journal of Agricultural Sciences, 2026)
This study examined how deagriculturalisation has impacted CO₂ emissions in India from 1990–2023. Although structural economic change is often seen as a sign of progress, little is known about how it affects the environment, especially in large emerging economies experiencing rapid urban and industrial growth. Using a Bayesian Vector Autoregression model with Minnesota priors, we estimated both short-term and long-term emission responses to the contraction of the agricultural sector in 2025. Our findings showed that a 1% decrease in agriculture’s GDP share led to an immediate 0.22% increase in CO2 emissions, which accumulated to 1.5% over ten years. This ongoing rise resulted from land-use changes, coal-intensive industrialisation, and urban sprawl that displaced carbon-absorbing croplands. Impulse response functions showed asymmetric dynamics: declines in agriculture drive emissions more strongly than growth reduces them. Energy consumption and industrialisation were the primary drivers of emissions, while high-tech exports offered only minor decarbonisation benefits. These results challenged the idea that sectoral diversification automatically supports climate goals. To reach India’s Net Zero 2070 target, policies need to decouple industrial growth from fossil fuels, such as transforming coal corridors into green hydrogen hubs, and include agroecological zoning to protect carbon-rich agricultural lands. This research provided empirical evidence to fill a key policy gap of how to manage structural change without locking in high emissions.